2021
DOI: 10.31616/asj.2019.0234
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Total Disc Replacement and Heterotopic Ossification: A Review of Literature Outcomes and Biomechanics

Abstract: Anterior cervical discectomy and fusion (ACDF) immobilizes surgical segments and can lead to the development of adjacent segment degeneration and adjacent segment disease. Thus, cervical total disc replacement (CTDR) has been developed with the aim to preserve the biomechanics of spine. However, heterotopic ossification (HO), a complication following CTDR, can reduce the segmental range of motion (ROM) and defects the motion-preservation benefit of CTDR. The pathological process of HO in CTDR remains unknown. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 85 publications
0
10
0
Order By: Relevance
“…Motion-limiting HO is undesirable and negates the purpose of motion-preserving TDR. It has been reported that implanting TDRs of greater heights has been associated with developing HO 10–12. This may be related to the biomechanical studies finding that implanting a TDR that is greater that natural height reduces ROM of the operated segment 17,18.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Motion-limiting HO is undesirable and negates the purpose of motion-preserving TDR. It has been reported that implanting TDRs of greater heights has been associated with developing HO 10–12. This may be related to the biomechanical studies finding that implanting a TDR that is greater that natural height reduces ROM of the operated segment 17,18.…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that implanting TDRs of greater heights has been associated with developing HO. [10][11][12] This may be related to the biomechanical studies finding that implanting a TDR that is greater that natural height reduces ROM of the operated segment. 17,18 The reduced motion may allow greater one growth around the prosthesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have suggested that the development of HO is a self-defense mechanism in response to the nonphysiological biomechanics of the cervical spine. 9,19 The exact mechanisms for the formation and development of HO following TDR remain unclear and needs further exploration. Zhou et al 15 reported in a 5-year follow-up study on 51 patients who underwent Bryan TDR and suggested that the so-called HO reflects progressive bone formation in individuals already predisposed to forming bone.…”
Section: Discussionmentioning
confidence: 99%